Pemanfaatan Teknologi Satelit untuk Monitoring Perubahan Ekosistem Mangrove dan Terumbu Karang - Budi Santoso (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2025)
The rapid degradation of coastal ecosystems, particularly mangroves and coral reefs, has become one of the most pressing environmental challenges in tropical regions. Conventional field-based monitoring methods are often limited by high costs, time, and accessibility, especially in remote areas. Satellite technology provides an effective alternative by offering large-scale, continuous, and multi-temporal monitoring of coastal ecosystems. This study aims to evaluate the application of satellite imagery in monitoring changes in mangrove and coral reef ecosystems in tropical regions. A multi-temporal remote sensing approach was employed using high-resolution satellite data, combined with ground truth surveys for validation. Results indicate that satellite technology can accurately detect changes in mangrove cover, identify coral bleaching events, and assess reef health conditions with significant spatial precision. Furthermore, the integration of satellite data with Geographic Information Systems (GIS) enhances ecosystem mapping, temporal trend analysis, and predictive modeling. This study highlights the crucial role of satellite-based monitoring in supporting coastal ecosystem management, conservation planning, and climate change adaptation strategies. The findings suggest that satellite remote sensing is not only efficient but also essential in establishing sustainable management practices for mangroves and coral reefs.